Quality assurance of company-based training in the dual system in Germany : an overview for practitioners and VET experts - Guellali, Chokri [Verfasser]; Sabbagh, Helena [Verfasser]; Achenbach, Michaela [Verfasser]; Biebeler, Hendrik [Verfasser]; Hemkes, Barbara [Mitarbeiter]; Pfaffe, Peter [Mitarbeiter]; Wölk, Markus [Mitarbeiter]; Zimmermann, Doris A. [Mitarbeiter] (Bundesinstitut für Berufsbildung, 2017)
"This brochure contains a structured overview of central quality assurance mechanisms which underlie the company-based part of initial training in the dual system in Germany. It informs about the most important regulations, procedures and stakeholders which secure and pursue the further development of training quality at the company as a learning venue. Addressed are education and training experts from the field of academic research, policy making and practice in Germany and Europe." (Editor, BIBB-Doku)
Keywords: S 1.3.1 Ausbildung im Dualen System; L 6.2 Qualitätsmanagement/Qualitätssicherung; S 3 Institutionen; Betriebliche Berufsausbildung; Duales System; Ausbildungsqualität; Qualitätssicherung; EQAVET